Avaliação da solubilização de fosfato por rizóbios isolados de leguminosas nativas dos Campos Gerais do Paraná. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Phosphorus (P) is a limiting nutrient for plant species and, consequently, for the balance of ecosystems. In the soil, P is found as phosphate ions associated with metals, which are not susceptible to incorporation by plant species. Phosphate sources can be bioavailable through phosphate solubilization, a process carried out by specialized groups of fungi and bacteria. The objective of this study was to evaluate the ability of phosphate solubilization by rhizobia isolated from root nodules of native leguminous plants from Campos Gerais, Paraná, Brazil, previously characterized genetically and physiologically. Initially, forty strains of the genera Paraburkholderia, Rhizobium and Bradyrhizobium were evaluated, of which fifteen showed solubilization of Ca3(PO4)2 in solid NBRIP medium. The five strains that showed the highest solubilization indices (IS) were all from the genus Paraburkholderia, were quantitatively and genetically characterized for such capacity. These strains had the solubilization of Ca3(PO4)2 quantified in liquid NBRIP presenting from 110.67 to 367.6 mg/L of soluble phosphate after seven days of incubation, accompanied by progressive acidification of the pH of the medium. A negative correlation was observed between acidification of the medium and the amount of P solubilized in liquid medium, unlike IS in solid medium. Due to this lack of correlation between the solubilization of phosphate in a liquid medium and in a solid medium, the quantification of the solubilizing capacity in a liquid medium was carried out for two other phosphate sources, FePO4 and AlPO4, whose tests in solid medium did not show solubilization on the part of no strain evaluated. These five strains showed solubilization from both sources when cultivated in liquid medium (1.42 to 4.49 mg/L in NBRIP + FePO4 and from 3.15 to 6.17 mg/L NBRIP + AlPO4). This result emphasizes the importance of the tests chosen for the selection of strains with the ability to solubilize phosphate, since, depending on the cultivation conditions and the phosphate sources used, strains that under other conditions could solubilize phosphate can be excluded. These five selected Paraburkholderia strains were further cultivated in NBRIP+Ca3(PO4)2 with different carbon sources, where the best IS were obtained with glucose in relation to mannitol and sucrose. Aiming at a better understanding of the genetic determinants of this ability, the sequencing and annotation of the genome of the strain Paraburkholderia sp. CNPSo 3281 as well as in silico analysis of genes related to phosphate solubilization of solubilizing species of the genus, including P. nodosa and P. guartelaensis. There was a relationship between presence/absence of genes and phylogeny of the evaluated Paraburkholderia. Genes for acid phosphatases were identified, as well as encoding enzymes active in the production of organic acids, such as gcd-pqq, for pyrroloquinoline-dependent glucose dehydrogenase, which is involved in the synthesis of gluconic acid, reported as the main organic acid involved in the solubilization of phosphate, among others. The presence of these genes may be associated with the production of organic acids, reductions in the pH values of cultures of these strains and solubilizing ability. The metabolic versatility of native strains of Paraburkholderia is highlighted, deserving further studies regarding its implication in the sustainability of terrestrial ecosystems as well as biotechnological viability.
Keywords: Paraburkholderia; BPCP; genômica; solubilização de fosfato inorgânico; Paraburkholderia; PGPR; genomic; inorganic phosphate solubilization; CNPQ::CIENCIAS BIOLOGICAS